Tuberculosis: the plague of the 21st century - Seas Ramos, Carlos (2008)
Tuberculosis, also known as the white plague, is a transmissible disease that is disseminated through airborne droplets. Personas affected by pulmonary tuberculosis are the source of infection. When a sick patient coughs, sneezes, speaks or spits, he/she sheds tuberculous bacilli to the environmental air. Inhaling a small number of such microorganisms is enough to catch the infection.